A Prospective Analysis of the Correlation Between Postoperative Pain and Vital Pulp Therapy - Shallal-Ayzin, Mark; Trinh, Tam; Yeung, William; Tawil, Peter Z.; Haggerty, Carol L.; Wu, Di; Khan, Asma A. (Frontiers in Dental Medicine, 2021)
Vital pulp therapy (VPT) is a viable treatment option for carious teeth with exposed pulps. To our knowledge, no study has examined the correlation between postoperative pain and the outcome of VPT on asymptomatic permanent teeth. The aim of this study was to examine whether odontogenic pain experienced after VPT on asymptomatic teeth with a carious pulp exposures is correlated with the progression of pulpal disease into a more inflamed or necrotic state. Direct pulp caps or partial pulpotomies using a tricalcium silicate (MTA Angelus, Angelus, Londrina, Brazil) were performed on asymptomatic permanent teeth using a standardized protocol. Patients were contacted at 24 h, 1 week, and 3 months following treatment and data was collected on post-operative pain and analgesic intake using a standardized questionnaire. At 6 months after treatment, an in-person clinical exam was performed which included standard vitality tests along with exposure of a periapical radiograph. Success was defined as an asymptomatic, functional tooth without any clinical or radiographic pathology. Data was analyzed using logistic regression. VPT was successful in 84.3% of patients at the 6 months timepoint. The percentage of patients that experienced pain at 24-h, 1 week, and 3-month time periods was 38, 22, and 12%, respectively. Pain at 3 months was significantly correlated with decreased outcome (p = 0.028). This data suggests that postoperative pain in the first 3 months after VPT is predictive of a poor treatment outcome.